EVALUASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DESA RANGKAH KIDUL KECAMATAN SIDOARJO KABUPATEN SIDOARJO - Firdanada Ristriannisa; Indah Prabawati (Universitas Negeri Surabaya, 2022)
Minister of Agrarian Regulation Number 6 of 2018 concerning Complete Systematic Land Registration (PTSL) is the Government's effort to resolve land disputes. PTSL is implemented in one village/kelurahan area. One of the villages implementing the 2019 PTSL program is Rangkah Kidul Village, Sidoarjo District, Sidoarjo Regency. This study aims to describe the evaluation of the PTSL program in Rangkah Kidul Village. This study uses a qualitative approach with descriptive research methods. The data collection techniques used were in-depth interviews, participant observation, documentation, and source triangulation techniques. Data analysis techniques used are data collection, data condensation, data presentation and drawing conclusions. The results of the study found that the implementation of the PTSL program in Rangkah Kidul Village on the effectiveness indicators was successfully accepted by the community according to the goals, foundations, and achievements of the PTSL program; efficiency is implemented with sufficient manpower, budget, facilities and infrastructure for the PTSL process, however, obstacles caused the distribution of certificates to experience a setback from the specified target; adequacy is not appropriate because not all communities have proof of land; the alignment is appropriate because all PTSL officers have provided equal opportunities, services, and information to all residents; responsiveness is appropriate because the PTSL program in this village is well received by the community and implementers respond to obstacles; The accuracy is appropriate because the PTSL program is precisely carried out in Rangkah Kidul Village and the community receives benefits. It is recommended that village PTSL officers be able to detect evidence of previous lands swiftly, Sidoarjo Regency BPN and village PTSL officers coordinate with each other to immediately process files that are not constrained, and provide targets to village PTSL officers.